Pengembangan Profesionalisme Guru Praktikan Melalui Program PPL: Studi Kasus Mahasiswa STAIN Madina di SMP Negeri 1 Panyabungan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the professional development of intern teachers through the Field Experience Practice Program (PPL) with a focus on STAIN Mandailing Natal (Madina) students at SMP Negeri 1 Panyabungan. Specifically, this study explores how practical field experience contributes to pedagogical and professional learner competencies. The research method used is a case study with a qualitative approach. Data were collected through participatory observation of student teaching activities, in-depth interviews with supervising teachers and student interns, and documentation of PPL reports. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that the PPL program plays a significant role in improving the professionalism of intern teachers, especially in terms of classroom management skills and learning tool development. The close relationship between intensive guidance from mentor teachers (methods) and adaptation to the school environment has proven to be key factors in transforming students' identities from practitioners to prospective professional teachers. However, challenges arise in synchronizing academic theory with classroom realities, necessitating enhanced clinical supervision throughout the program. This study provides a theoretical contribution to the collaborative clinical mentoring model between state religious universities and public schools in creating an adaptive learning ecosystem in the era of digital disruption